2000
DOI: 10.1037/1064-1297.8.4.524
|View full text |Cite
|
Sign up to set email alerts
|

The analgesic potential of intraventricular polymer-encapsulated adrenal chromaffin cells in a rodent model of chronic neuropathic pain.

Abstract: Adrenal chromaffin cells reportedly produce analgesic effects when implanted in the periaqueductal gray and the intrathecal space near the spinal cord. Chromaffin cells implanted in the cerebral ventricles may also produce analgesic effects, and the availability of the cerebral ventricles as a potential implant site could be advantageous for some patients. In fact, some of the first patients were implanted in the intraventricular site, even though the analgesic potential of that site had never been demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…However, antinociception following chromaffin cell transplants produces controversial results in animal studies. For example, implantation of primary cultured human chromaffin cells has been observed in several chronic pain models [29,30], while bovine chromaffin cell grafts were shown to demonstrate no analgesic effect on acute or tonic pain in a rat formalin model [31,32]. It is suggested that the failure to produce antinociception might be due to inadequate amounts of grafted chromaffin cells, as well as low levels of met-enkephalin and catecholamines.…”
Section: Resultsmentioning
confidence: 99%
“…However, antinociception following chromaffin cell transplants produces controversial results in animal studies. For example, implantation of primary cultured human chromaffin cells has been observed in several chronic pain models [29,30], while bovine chromaffin cell grafts were shown to demonstrate no analgesic effect on acute or tonic pain in a rat formalin model [31,32]. It is suggested that the failure to produce antinociception might be due to inadequate amounts of grafted chromaffin cells, as well as low levels of met-enkephalin and catecholamines.…”
Section: Resultsmentioning
confidence: 99%